2003
DOI: 10.1046/j.1523-1755.2003.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and progression of nephropathy in type 2 diabetes: The United Kingdom Prospective Diabetes Study (UKPDS 64)

Abstract: The proportion of patients with type 2 diabetes who develop microalbuminuria is substantial with one quarter affected by 10 years from diagnosis. Relatively fewer patients develop macroalbuminuria, but in those who do, the death rate exceeds the rate of progression to worse nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
988
13
66

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,557 publications
(1,141 citation statements)
references
References 49 publications
51
988
13
66
Order By: Relevance
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Besides macrovascular complications, microangiopathy represents a major burden and seems more strongly linked to chronic hyperglycaemia than macroangiopathy, both in T1DM [57] andT2DM [6]. It has a major impact on the quality of life but also reduces life expectancy, especially when diabetic nephropathy is present [58]. All diabetic retinopathy end points (including proliferative retinopathy, macular edema, and vision-threatening retinopathy) increases with diabetes duration and poor glucose control (assessed by high HbA1c), although their prevalence is higher in people with T1DM compared with T2DM [59].…”
Section: B) Non-inferiority Trialsmentioning
confidence: 99%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Besides macrovascular complications, microangiopathy represents a major burden and seems more strongly linked to chronic hyperglycaemia than macroangiopathy, both in T1DM [57] andT2DM [6]. It has a major impact on the quality of life but also reduces life expectancy, especially when diabetic nephropathy is present [58]. All diabetic retinopathy end points (including proliferative retinopathy, macular edema, and vision-threatening retinopathy) increases with diabetes duration and poor glucose control (assessed by high HbA1c), although their prevalence is higher in people with T1DM compared with T2DM [59].…”
Section: B) Non-inferiority Trialsmentioning
confidence: 99%
“…W hen kidney function declines, death from cardiovascular disease (CVD) predominates over progression of chronic kidney disease (CKD) (1)(2)(3). Excess CVD risk even in early-stage CKD is not fully explained by traditional, Framingham-type CVD risk factors.…”
mentioning
confidence: 99%
“…[16][17][18] This phenomenon is clearly observed in patients with type II DM, in which ¼ of the patients presents with renal compromise after ten years of disease. 19 Proteinuria was also associated with higher mortality rates, as published by other authors who demonstrated this is a risk factor that is not connected to cardiovascular mortality. 20,21 On the other hand, the relation between the use of statins and lower mortality rates, as well as the slower progression to renal function failure with the need for RRT, is controversial.…”
Section: Discussionmentioning
confidence: 54%